Coordination compounds of indium, gadolinium, and erbium nitrates with low urea content - E. V. Savinkina; I. A. Karavaev; E. K. Bettels; G. A. Buzanov; A. S. Kubasov (Тонкие химические технологии)
Objectives. To date, compounds of rare earth nitrates with urea in a ratio of 1:4 and indium in a ratio of 1:6 have been synthesized and structurally characterized. However, there is a lack of research into similar compounds having a lower urea content. The purpose of this work was to continue the search for regularities of structure formation for complexes of various elements with urea.Methods. Novel coordination compounds were synthesized and characterized by powder- and single-crystal X-ray diffraction analysis, as well as infrared spectroscopy.Results. The interaction of indium, gadolinium and erbium nitrates with urea (Ur) in an aqueous solution under conditions of ligand deficiency produces the previously unknown coordination compounds cis-[In(Ur)4(NO3)2]NO3, [Gd(H2O)2(Ur)2(NO3)3], and [Er(H2O)2(Ur)(NO3)3]. The indium complex is shown to have an ionic structure, whereas the gadolinium and erbium complexes have a molecular structure. In the indium complex, the coordination number is 6; the cation has an octahedral structure; it involves two cis-arranged monodentate nitrate groups and four monodentate urea molecules. The coordination number of gadolinium is 10; here, the coordination polyhedron is a distorted pentagonal bipyramid at the vertices of which there are two water molecules, while in the internal polygonal base there are two monodentate urea molecules and three bidentate chelating nitrate groups oriented perpendicular to the polygonal base of the bipyramid. The coordination number of erbium is 9; the coordination polyhedron is a distorted tricapped trigonal prism.Conclusions. In contrast with the gadolinium complex, one urea molecule is coordinated in the erbium complex instead of two, decreasing the coordination number from 10 to 9. In the indium complex cation, the coordination number is 6; unlike the gadolinium and erbium complexes, the cation does not contain water, and the nitrate groups are monodentate.